Immunomodulatory effect of macrolides: At what cost?. (2016) - Kipourou, Maria; Manika, Katerina; Papavasileiou, Apostolos; Pitsiou, Georgia; Lada, Martha; Ntinapogias, Evangelos; Kioumis, Ioannis
Abstract: We present the case of a 60-year old female patient, with a 10 year history of non-CF bronchiectasis and use of macrolides as maintenance immunomodulatory treatment, who was diagnosed with macrolide-resistant Mycobacterium avium complex lung disease. Macrolides' immunomodulatory effect is appealing for non- CF bronchiectasis patients, hiding a high risk for resistance emergence.